Development and validation of a CD4+/CD8+ ratio-based nomogram to predict plastic bronchitis in pediatric Mycoplasma pneumoniae pneumonia - Lian, Di; Lin, Chenye; Dong, Xiangmei; Wei, Jianxing; Huang, Xueling; Jiang, Hongman; Tang, Qiuyu (Frontiers in Pediatrics, 2025)
IntroductionPlastic bronchitis (PB) is a rare but severe complication of Mycoplasma pneumoniae pneumonia (MPP) in children. Early identification of PB is critical for timely intervention. This study aimed to develop and validate a nomogram incorporating the CD4+/CD8 + ratio to predict PB risk in children with MPP who underwent bronchoscopy.MethodsThis single-center, retrospective cohort study was conducted at Fujian Children's Hospital, China, from January 2023 to December 2024. A total of 281 children hospitalized with MPP, including 39 patients who developed PB, were included. Key predictors for nomogram were selected out of 19 variables using least absolute shrinkage and selection operator regression, followed by multivariable logistic regression. Model performance was evaluated through discrimination, calibration, and decision curve analysis (DCA). Internal validation was performed using the Bootstrap method with 1,000 resamples.ResultsThe nomogram incorporated four independent predictors—fever duration, atelectasis, elevated D-dimer, and reduced CD4+/CD8 + ratio. It demonstrated strong discrimination (AUC = 0.83, 95% CI 0.77–0.90) and calibration (Hosmer-Lemeshow P = 0.303), with superior net benefit across risk thresholds of 0.1–0.7 by decision curve analysis, supporting its clinical utility for early risk stratification. Bootstrap validation confirmed robust performance with minimal overfitting.DiscussionCD4+/CD8 + ratio based nomogram provides a practical tool for predicting PB risk in children with MPP, which may facilitate early bronchoscopy leading to improved patient outcomes.